A study on the process of apparel retailing at redemptorist road, Baclaran - Mutuc, Bernadette Cruz
Baclaran is often associated with the Redemptorist Church where a substantial number of devotees flock to pay homage to Our Lady of Perpetual Help. Aside from this, Baclaran has gained popularity among the Filipinos because of the availability of various dry goods on sale at bargain prices. As a consequence of which, this study aimed to analyze the process of apparel retailing, specifically at the Redemptorist Road, Baclaran. The foremost goal of the study was to investigate about the process of apparel retailing conducted by retailers in Baclaran particularly with stalls alongside the Redemptorist Road. Specifically, it aimed to: determine the formation of the apparel retailing business, know the internal organization of the specific apparel retailers, determine how apparel retailers acquire their merchandise, determine how apparel retailers distribute their merchandise and lastly, identify the problems encountered by the apparel retailers. For purposes of this study, the term "process" shall be divided into four stages: the formation of the retail business, internal organization, acquisition of merchandise and distribution of merchandise. The study was limited to the Redemptorist Road encompassing a span of less than a kilometer. Only stalls engaged in selling ready-to-wear apparel for men and women were included in the study. The stalls included were those situated alongside the Redemptorist Road. Due to limited time and financial constraints, only fifteen out of one hundred thirty-nine retailers in the mentioned location were included in the study. The methodology employed by the researcher was the descriptive approach. Questionnaires were distributed to willing participants and interview were conducted to further aid in data gathering. An analysis of the data gathered was also included and percentage tables were provided. The study revealed that some retailers obtained their merchandise from neighboring countries specifically Thailand (Bangkok), Hong Kong, Indonesia (Jakarta) and others obtained their merchandise from the Chinese and Taiwanese wholesalers who peddled their goods near the LRT-fire department station located in Baclaran. Results revealed that most of the retailers did not engage the services of hired helpers or employees, but instead owned and managed their business on their own. Their customers were also not confined to a particular class; rather their customers belong to the categories of Class A, B, and C of the socio-economic status. There is a need for the apparel retailers situated alongside the Redemptorist Road to evaluate their merchandise to be able to compete effectively with those engaged in apparel retailing located at high-end metropolitan districts. This is so because of the common conception of the Filipinos that apparel obtained from well-known malls and branded boutiques are of better quality and higher class. In addition, the increasing popularity of "ukay-ukay" clothes (secondhand clothing) at cheap prices poses a threat to the survival of the apparel retailing. It is important for apparel retailers to anticipate what the customers want and need so as to provide better services for the Filipinos and ensure a profitable source of livelihood for the retailers as well.